History of Philosophy and the Reflective Society - Pozzo, Riccardo (De Gruyter, 2021)
Make believe we are in 2028, attending the 26th World Congress of Philosophy, then the question is: how will philosophers delve into historic texts? Not on paper, but on devices. And each philosophical proposition uttered by any philosopher at any time will not stay on its own. It will instead be co-created by many others. The history of philosophy will be participative, thus contributing to the establishment of a reflective and inclusive society.